Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Pegawai Ditjen Kuathan Kemhan RI - Sutiyawati; Murniyati (CV Warnak Johanna Nusantara, 2026)
Human Resource Management (HR) plays a strategic role in achieving organizational goals through the management, development, and maintenance of a quality workforce. Employee competence, which is reflected in knowledge, skills, and professionalism, directly influences individual performance, while work discipline through compliance with rules and responsibilities is an important factor in achieving organizational targets. This study was compiled with the aim of analyzing the influence of competence and work discipline on employee performance of the Directorate General of Defense Forces, Ministry of Defense of the Republic of Indonesia. This study uses a quantitative method with a statistical test approach. Data were collected through observation, interviews, literature studies, and questionnaires distributed to 40 respondents of HR Directorate employees of the Directorate General of Defense Forces, Ministry of Defense. Data analysis techniques include t-test, f-test, multiple linear regression, and coefficient of determination using SPSS version 26. The results of the study indicate that partially, the variables of competence and work discipline have a positive and significant effect on employee performance, evidenced by the calculated t-value being greater than the t-table. Simultaneously, competence and work discipline also significantly influence performance, as indicated by the calculated f-value being greater than the table f-value. The coefficient of determination test indicates that both variables play a significant role in improving employee performance